A new species and notes on Perlidae (Plecoptera) from Paraná and Santa Catarina States, southern Brazil - Novaes, Marcos Carneiro [UNESP]; Bispo, Pitágoras da Conceição [UNESP] (Magnolia Press, 2014)
Specimens of Perlidae (Plecoptera) deposited in the Entomological Collection Padre Jesus S. Moure of the Universidade Federal do Parana and additional material recently collected in Parana and Santa Catarina states, Brazil were studied. Six previously described species were identified, Anacroneuria debilis (Pictet, 1841), A. cathia Froehlich, 2002, A. polita (Burmeister, 1839), A. trimacula Jewett, 1959, Kempnyia neotropica (Jacoson and Bianchi, 1905) and K. colossica (Navas, 1934). Additionally, a new species, Anacroneuria iguazu n. sp is described.
Keywords: Aquatic insects; Streams; Biodiversity; Neotropical